Mechanical Fabric and In-Situ Stress Orientations in the Devonian Gas Shales of the Appalachian Basin - William J. Gregg (Society for Mining, Metallurgy & Exploration, 1986)
Mechanical testing results on oriented Devonian gas shale core throughout the Appalachian basin show a preferred fracture direction perpendicular to bedding. The preferred direction is generally parallel to the Allegheny Front, but is only coincidentally parallel with in-situ stresses in some areas of the basin. The strength of the preferred orientation of induced fractures decreases with distance from the Front. It is suggested that strain related to Paleozoic deformation is responsible for this mechanical fabric and thus the direction of induced fractures in laboratory tests may not be of use as indicators of in-situ stress orientations as previously suggested.